2008
DOI: 10.3382/ps.2007-00353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rabbit Sacculus Rotundus Antimicrobial Peptides on the Intestinal Mucosal Immunity in Chickens

Abstract: Ninety chickens were randomly divided into 2 groups (45 chickens in each group) to determine the effect of oral administration of rabbit sacculus rotundus antimicrobial peptides (RSRP) on the intestinal mucosal immune responses in chicken. On d 7, 14, 21, and 28, the animals received 0.1 mg of RSRP dissolved in 0.5 mL of physiological saline. The control groups received the same dose of physiological salt solution on the same day. The results showed that RSRP increased the villus height of the duodenum (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 19 publications
6
34
0
Order By: Relevance
“…Intestine morphology may be mediated via alteration of intestinal microflora. It was shown that, the digestive function of the small intestine is closely related to mucosal architecture and villi structure (Liu et al, 2008). Few reports are available that have compared the effect of probiotic types on broiler intestine morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Intestine morphology may be mediated via alteration of intestinal microflora. It was shown that, the digestive function of the small intestine is closely related to mucosal architecture and villi structure (Liu et al, 2008). Few reports are available that have compared the effect of probiotic types on broiler intestine morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The histological sections (4 µm) were immersed in citrate buffer solution (0.01 M, pH6.0) and heated at 120°C in autoclaved sterilizer for 10 min, naturally cooled for 30 min, and then immersed in 3% aqueous hydrogen peroxide (H 2 O 2 ) for endogenous peroxidase ablation at room temperature for 30 min. The following steps were executed in a moist chamber and this procedure has been exclusively described by Liu et al [51]. Briefly, the histological sections were washed in PBS, quenched with blocking buffer (Zymed Laboratories Inc., San Diego, USA).…”
Section: Methodsmentioning
confidence: 99%
“…may contribute to the growth of the embryos as reported previously (Liu et al, 2008;Bao et al, 2009;Wang et al, 2009). To further investigate the effect of SIAMP on the inhibition of IBV, we measured the agglutination titer of allantoic fluid of the chick embryos.…”
Section: Swine Intestine Antimicrobial Peptidesmentioning
confidence: 96%